The Relationship between Clinico-biochemical Characteristics and Psychiatric Distress in Young Women with Polycystic Ovary Syndrome - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2008)
The relationship between clinico-biochemical characteristics and self-reported psychological parameters in 42 women with polycystic ovary syndrome (PCOS) and 42 age-matched healthy controls was examined. The General Health Questionnaire was used (GHQ-12) to ascertain emotional distress and the Beck Depression Inventory (BDI) to determine depressive symptoms. Emotional distress, depressive symptoms, hirsutism score, body mass index (BMI), waist-to-hip ratio (WHR), luteinizing hormone/follicle-stimulating hormone ratio, serum total testosterone, dehydroepiandrosterone sulphate levels and the insulin resistance index were significantly greater in women with PCOS than in healthy women. The BDI and GHQ-12 scores of the women with PCOS were significantly higher than those of the control group (BDI, 11.69 +/- 9.49 vs 5.80 +/- 4.58; GHQ-12, 3.38 +/- 3.38 vs 1.54 +/- 1.97, respectively), and BMI and WHR were positively correlated with the BDI and GHQ-12 scores. Clinicians should be aware of the increased risk of emotional distress and depression in women with PCOS, especially those who are obese, and of the need to screen these patients for such symptoms.
Keywords: POLYCYSTIC OVARY SYNDROME; DEPRESSIVE SYMPTOMS; EMOTIONAL DISTRESS; PSYCHIATRIC DISTRESS; OBESITY; GENERAL HEALTH QUESTIONNAIRE; MENTAL HEALTH; QUALITY-OF-LIFE; INSULIN-RESISTANCE; MAJOR DEPRESSION; OBESITY; RISK; HIRSUTISM; ANDROGENS; SYMPTOMS; GLUCOSE; WEIGHT